Saprotrophic litter fungi in a Mediterranean ecosystem: Behaviour on different substrata - Pasqualetti, M.; Mulas, B.; Rambelli, A.; Tempesta, S. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
Saprotrophic fungi sporulating on 17 types of leaf litter collected during the dry season in the Sardinian Mediterranean area were analysed. The fungal assemblages identified in each substratum showed an overlap value ranging from 5.9 to 46.7%. A consistent connection between certain fungal species and their substrata was detected; among the 168 fungal species identified, 104 (62%) may be regarded as specialised. Each fungal species was characterised according to morphological and ecological features. Multidimensional scaling (MDS) showed that ubiquitous and common species have morphological characters distinguishing them from specialised species.
doi: 10.1080/11263504.2013.877534doi: 10.1080/11263504.2013.877534The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: litter decomposition; Mediterranean ecosystem; saprotrophic fungi